Social Behavior Observer Checklist: Patterns of Spontaneous Behaviors Differentiate Patients With Neurodegenerative Disease From Healthy Older Adults - Rankin, Katherine P.; Toller, Gianina; Gavron, Lauren; La Joie, Renaud; Wu, Teresa; Shany-Ur, Tal; Callahan, Patrick; Krassner, Maggie; Kramer, Joel H.; Miller, Bruce L. (Frontiers in Neurology, 2021)
Neurodegenerative disease syndromes often affect personality and interpersonal behavior in addition to cognition, but there are few structured observational measures of altered social demeanor validated for this population. We developed the Social Behavior Observer Checklist (SBOCL), a 3-minute checklist tool, to facilitate identification of patterns of interpersonal behavior that are diagnostically relevant to different neurodegenerative syndromes. Research assistants without formal clinical training in dementia used the SBOCL to describe participants’ behavior, including 125 healthy older adults and 357 patients diagnosed with one of five neurodegenerative disease syndromes: 135 behavioral variant frontotemporal dementia (bvFTD), 57 semantic variant primary progressive aphasia (svPPA), 51 nonfluent variant PPA (nfvPPA), 65 progressive supranuclear palsy (PSP), and 49 amyloid-positive Alzheimer’s disease syndrome (AD), all of whom had concurrent 3D T1 MRI scans available for voxel-based morphometry analysis. SBOCL item interrater reliability ranged from moderate to very high, and score elevations showed syndrome-specific patterns. Subscale scores derived from a degree*frequency product of the items had excellent positive predictive value for identifying patients. Specifically, scores above 2 on the Disorganized subscale, and above 3 on the Reactive and Insensitive subscales, were not seen in any healthy controls but were found in many patients with bvFTD, svPPA, nfvPPA, PSP, and AD syndromes. Both the Disorganized and Reactive subscale scores showed significant linear relationships with frontal and temporal gray matter volume that generalized across syndromes. With these initial psychometric characteristics, the SBOCL may be a useful measure to help non-experts identify patients who are appropriate for additional specialized dementia evaluation, without adding time to patient encounters or requiring the presence of an informant.